Verbs or Nouns - Which Sound More Natural in Vietnamese and Implications for English and Translation Teaching to Vietnamese Students - Thuy, Pham Thi (VNU Journal of Foreign Studies; Vol 32 No 2, 2016)
Abstract: What are culturally specific linguistic features of Vietnamese texts? A comparison of five Australian short stories and their translation texts in Vietnamese has revealed one of the features, a mismatch in the word classes: several nouns in English are shifted to verbs in Vietnamese. To answer the question whether verbs sound more natural than nouns in Vietnamese, the present study measured recipients” responses to the naturalness of sentences containing verbs in the translation texts, which had been translated from nouns in the original texts. The study, following Bachman”s  (1990) framework, employed the method of Multiple-choice Discourse Completion Tasks (MDCT). The results of the study, conducted on 370 native speakers of Vietnamese, confirm previous findings on Vietnamese communicative preferences, that are linguistically manifest (Trần Ngọc Thêm, 1998). The implications of this can be useful for teaching English, in general, and teaching translation, in particular, to Vietnamese students. Keywords: English – Vietnamese fictional prose translation, word class shift, culturally specific linguistic features, L1 naturalness, Multiple-choice Discourse Completion Task .